Personality Traits, Risk-Taking Behaviors And Self-Regulation In Young Adults - Nisa, Mehar-un-; PhD, Rabia Maryam; PhD, Abida Kareem; Khan, Imran (Migration Letters, 2024)
BACKGROUND Personality traits intricately intertwine with risk-taking behaviors across health, finance, and social domains. The Five Factor Model posits that heightened extraversion and diminished neuroticism correlate with increased propensities for risk-taking. The essential in this dynamic is self-regulation, serving as the crucial mediator between personality traits and risk behaviors. PARTICIPANTS AND PRODUCE A cross-sectional research consisted of sample size 400 young adults (200 men; 200 women) with an age range of 18-25 years (Mage = 21.16, SDage = 1.802) using convenient sampling technique. The instruments used in the study were Mini International Personality Items Pool (IPIP, Donnellan et al., 2006), Domain-Specific Risk-Taking Scale (DOSPERT, Weber & Blais, 2006), and Short Self-Regulation Questionnaire (SSRQ, Carey et al., 2004). RESULTS The results of the research indicated that the personality traits (extroversion, openness, conscientiousness) were significantly positive correlation with risk-taking while the personality traits (agreeableness, neuroticism) had not significant effect on risk-taking. The self-regulation had negative significant relationship with risk-taking behaviors and predictor of these behaviors. The extroversion and openness were the predictor of the risk-taking rather than the other personality traits. The self-regulation was the partial mediator between the personality traits and risk-taking behaviors. The t-test results indicated the gender difference in risk-taking behaviors women performed less risk-taking behaviors as compared to the men and the open-ended questions also showed[1] that men smoked and vaped more as compared to women. CONCLUSION The results pointed out the importance of the personality traits and self-regulation in the risk-taking behaviors. The findings of this study hold several significant implications across different domains like mental health, personalized interventions, career paths that align with their risk tolerance and policy making.